Impactos da pandemia na educação de surdos em uma escola bilíngue pública de manaus - Santos, Andréia Carvalho dos (BRASIL, 2023)
In 2020, we had a Covid-19 pandemic, which affected education in general, as well as the education of the deaf. The bilingual school for the deaf in Manaus was chosen for application and data analysis according to the research theme. This work had the general objective of bringing reflections on the effects of the pandemic on the education of the deaf in the selected school (EEACS). And as specific objectives to verify the impacts on their education, understand the role played by the family in this period and investigate what were the strategies used for teaching deaf students in fundamental II. The theoretical foundation permeates public policies in bilingual education for the deaf with specific legislation, the effects of the pandemic in Amazonas, the use of technologies in education, Bilingual Education for the deaf, we highlight the authors (Quadros, 2008; Faria-Nascimento, 2021) , and remote teaching in the Literature Libras course at UFAM in the pandemic period, (Oliveira; Carvalho; Dolzane, 2022). The methodology is a bibliographic review (Lakatos and Marconi, 2003), with a qualitative approach and an exploratory method (GIL, 2002), through standardized interviews (Lodi, 1974). This investigation outline with nine participants, being teachers of the reference school, SEDUC and UFAM. A presentation and discussion of the data analysis of this research was carried out, through clippings of the responses of the preparations according to the theme of this work (Ladd, 2013; Skliar, 2016; Strobel, 2008). This research brings reflections and contributions regarding how classes were at EEACS, during the pandemic and post-pandemic.